Breath : the new science of a lost art - Nestor, James (Riverhead Books, an imprint of Penguin Random House LLC, 2020)
"No matter what you eat, how much you exercise, how resilient your genes are, how skinny or young or wise you are, none of it matters if you're not breathing properly. There is nothing more essential to our health and wellbeing than breathing: take air in, let it out, repeat 25,000 times a day. Yet, as a species, humans have lost the ability to breathe correctly, with grave consequences. Science journalist James Nestor travels the world to figure out what went wrong with our breathing and how to fix it. Why are we the only animals with chronically crooked teeth? Why didn't our ancestors snore? Nestor seeks out answers in muddy digs of ancient burial sites, secret Soviet facilities, New Jersey choir schools, and the smoggy streets of Sao Paulo, Brazil. He tracks down men and women exploring the science behind ancient breathing practices like Pranayama, Sudarshan Kriya, and Tummo and teams up with pulmonary tinkerers to scientifically test long-held beliefs about how we breathe. Modern research is showing us that changing the ways in which we breathe can jump-start athletic performance, halt snoring, rejuvenate internal organs, mute allergies and asthma, blunt autoimmune disease, and straighten scoliotic spines. None of this should be possible, and yet it is. Drawing on thousands of years of medical texts and recent cutting-edge studies in pulmonology, psychology, biochemistry, and human physiology, Breath turns the conventional wisdom of what we thought we knew about our most basic biological function on its head. You will never breathe the same again"--